Resistance for genotoxic damage in mesenchymal stromal cells is increased by hypoxia but not generally dependent on p53-Regulated cell cycle arrest - Lützkendorf, Jana; Wieduwild, Elisabeth; Nerger, Katrin; Lambrecht, Nina; Schmoll, Hans-Joachim; Müller-Tidow, Carsten; Müller, Lutz P. (PLOS ONE, 2017)
Adult stem cells including multipotent mesenchymal stromal cells (MSC) acquire a high amount of DNA-damage due to their prolonged lifespan. MSC may exert specific mechanisms of resistance to avoid loss of functional activity. We have previously shown that resistance of MSC is associated with an induction of p53 and proliferation arrest upon genotoxic damage. Hypoxia may also contribute to resistance in MSC due to the low oxygen tension in the niche. In this study we characterized the role of p53 and contribution of hypoxia in resistance of MSC to genotoxic damage. MSC exhibited increased resistance to cisplatin induced DNA-damage. This resistance was associated with a temporary G2/M cell cycle arrest, induction of p53- and p21-expression and reduced cyclin B / cdk1-levels upon subapoptotic damage. Resistance of MSC to cisplatin was increased at hypoxic conditions i. e. oxygen <0.5%. However, upon hypoxia the cisplatin-induced cell cycle arrest and expression of p53 and p21 were abrogated. MSC with shRNA-mediated p53 knock-down showed a reduced cell cycle arrest and increased cyclin B / cdk1 expression. However, this functional p53 knock down did not alter the resistance to cisplatin. In contrast to cisplatin, functional p53-knock-down increased the resistance of MSC to etoposide. We conclude that resistance of MSC to genotoxic damage is influenced by oxygen tension but is not generally dependent on p53. Thus, p53-dependent and p53-independent mechanisms of resistance are likely to contribute to the life-long functional activity of MSC in vivo. These findings indicate that hypoxia and different resistance pathways contribute to the phenotype that enables the prolonged lifespan of MSC.
Gesehen am 26.11.2024